The Level of Knowledge of The Elderly, Family Support and The Role of Cadres on The Utilization of The Elderly Integrated Health care Post (HEALTH CARE: JURNAL KESEHATAN, 2025)
The Elderly Integrated Healthcare Post (Posyandu) refers to an integrated health service site arranged for the elderly community that have been agreed upon and driven by the community. Achievement of elderly health coverage at the Kramatmulya Community Health Center was 62.3%. This study aims to determine the correlation between the level of knowledge of the elderly, family support, and the role of cadres with the utilization of the elderly posyandu. This was a quantitative study with cross sectional design. The study population involved the elderly in the work area of ​​Kramatmulya CHC by 6757 people. The study samples size was 67 people who were selected using the proportional random sampling technique. The instruments applied here were questionnaires and filling sheets. Data were collected through a structured interview and documentation study. Data were analyzed using the Chi Square test. The study findings revealed that 32 respondents (47.8%) had a poor level of knowledge, 39 respondents (58.2%) had a poor level of family support, 21 respondents (31.3%) admitted to observe poor role of cadres, and 40 respondents (59.7%) were less active in utilizing the elderly posyandu. The Chi Square test results showed that the level of knowledge (p-value = 0.000), family support (p-value = 0.000), and the role of cadres (p-value = 0.001) had a significant correlation with the utilization of the elderly posyandu